Proceedings of the 9th World Construction Symposium 2021 on Reshaping Construction: Strategic, Structural and Cultural Transfor 2021
DOI: 10.31705/wcs.2021.1
|View full text |Cite
|
Sign up to set email alerts
|

A framework to measure collaboration in a construction project

Abstract: Collaboration amongst stakeholders in a construction project plays a significant role in managing and completing a project successfully. It specifically helps in interface management amongst the stakeholders. Among the various aspects of collaboration, there are two key factors that predominant. Firstly, the psychological factors that define a person as a natural collaborator, and secondly, the project-level enablers that determine a collaborative project. Therefore, in this study, two inductive theories are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Kshaf et al, (2022) 19 factors that will improve the interaction between the subcontractor und the main contractor (Kshaf et al, 2022). Nath et al, (2021) identified ten project level enablers of collaboration (Nath 2021). Taherdoost & Brard (2019) identified 25 criteria in his study (Taherdoost & Brard, 2019).…”
Section: Existing Criteria For Supplier Selectionmentioning
confidence: 99%
“…Kshaf et al, (2022) 19 factors that will improve the interaction between the subcontractor und the main contractor (Kshaf et al, 2022). Nath et al, (2021) identified ten project level enablers of collaboration (Nath 2021). Taherdoost & Brard (2019) identified 25 criteria in his study (Taherdoost & Brard, 2019).…”
Section: Existing Criteria For Supplier Selectionmentioning
confidence: 99%
“…Mechanisms for measuring collaboration have been proposed, like [3] and [4], and research indicates that managers need tools to help evaluate teams and resources used [5]. Some tools propose a qualitative method [6].…”
Section: Introductionmentioning
confidence: 99%